2012
DOI: 10.3797/scipharm.1207-15
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Hippocampal 5-HT and DA Levels Following Sub-Chronic Exposure to Noise Stress: Impairment in both Spatial and Recognition Memory in Male Rats

Abstract: Mankind is exposed to a number of stressors, and among them noise is one which can cause intense stress. High levels of background noise can severely impair one’s ability to concentrate. The present study was aimed to investigate the effect of sub-chronic noise stress on cognitive behavior and hippocampal monoamine levels in male rats. The study was performed on 12 male Wistar rats, divided into two groups; the control and noise-exposed. The rats in the test group were subjected to noise stress, 4h daily for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Noise exposure exceeds 90 dB has been reported to be a source of stressor [4]. The adverse impact of noise on learning, memory and hippocampal neurogenesis has been reported by previous studies [5][6][7][8][9]. The mechanisms underlying the decline of memory after noise exposure are not entirely clear.…”
Section: Introductionmentioning
confidence: 92%
“…Noise exposure exceeds 90 dB has been reported to be a source of stressor [4]. The adverse impact of noise on learning, memory and hippocampal neurogenesis has been reported by previous studies [5][6][7][8][9]. The mechanisms underlying the decline of memory after noise exposure are not entirely clear.…”
Section: Introductionmentioning
confidence: 92%
“…The maze was elevated 60 cm high above the floor. The procedure and techniques were essentially the same as reported previously (Haider et al 2012b). The memory test was assessed during elevated plus maze experimental session in two trials (first day: learning and second day: retention of memory).…”
Section: Memory Function Tested By Elevated Plus Maze Testmentioning
confidence: 99%
“…Husain et al reported oral intubation of styrene in male rats increased serotonin levels (32). The role of serotonin (28,33) and dopamine (21) in the pathophysiology of anxiety has been clearly proven. Phenylglyoxylic acid as one of styrene metabolite had no effects on neurobehavior after using a functional observational battery or radial arm maze and increased dopamine concentration in the cerebellum, hippocampus, pons, and whole brain (34).…”
Section: Effect Of Styrene On Locomotor Activity Anxiety and Workinmentioning
confidence: 98%
“…The results showed that simultaneous exposure to noise and styrene decreased locomotor activity, while styrene or noise exposure alone had no significant effect on locomotor activity. Haider et al have shown that subchronic exposure to noise decreased the locomotor activity, whereas increased the concentration of dopamine in the brain and the rate of monoamine transmission (21).…”
Section: Effect Of White Noise On Locomotor Activity Anxiety and Womentioning
confidence: 99%
See 1 more Smart Citation